Clinico-epidemiological study of vitiligo in a tertiary care hospital of Eastern India - Jayanta Kumar Barua; Kaushiki Hazra; Prabal Samanta; Param Satsangi; Tirtharaj Saha; Professor Saswati Halder (Journal of Pakistan Association of Dermatologists, 2023)
Background Vitiligo is a common acquired pigmentary disorder with a worldwide incidence of 0.2-2% whereas in India it is 0.5-2.5%. Though having insignificant mortality, it causes heavy burden on the morbidity owing to its pycho-social impacts. Also, there is association with other autoimmune disorders like Type 1 diabetes Mellitus, thyroid disorder, pernicious anaemia, Inflammatory bowel disease, psoriasis, lichen planus, alopecia areata etc. There are several clinical variants like acrofacial, universalis, focal, segmental, mucosal etc. There are various treatment modalities both topical ( steroids, calcineurin inhibitors psoralens) as well as systemic like steroids, psoralens, cyclosporine and JAK inhibitors like Tofacitinib. Methods This is a clinico-epidemiological study conducted over a period of 6 months. Study population comprised of 100 consecutive patients attending the OPD. Written consent was provided to the patients followed by history taking and clinical examination. Severely ill, pregnant patients and those unwilling to participate were excluded. Study variables included both epidemiological and clinical parameters like age, sex, occupation, morphological type, age of onset, associated autoimmune diseases etc. Data collected was tabulated, analysed and compared with existing literature. Results Out of 100 patients enrolled in our study, majority (48%) belonged to the age of adolescents and young adults (11-30 yrs.), mean age being 28.4. 54% were females. Majority (45%) had access to primary education but not completing secondary exam. Most (35%) had onset in childhood (<12 yrs.), while majority had duration of disease between 1-10 yrs. (58%). Only 3% had family history of vitiligo. Most of them (79%) had no obvious triggering factor while Half of the patients had stable disease for more than 1 year. 87% of the patients did not have any association with any other autoimmune disorders. Generalised vitiligo (41%) was the most common subtype while only 1 patient had vitiligo universalis. 64% of the patients had received a combination of systemic and topical treatment before. Conclusion Our study provides an inight into the prevalence, socio-demographic factors and the various clinical parameters of vitiligo as well as their association with other autoimmune disorders. This study has also been compared with other studies conducted previously which shows the results of increased female preponderance, and generalised vitiligo being the most common subtype. In our study only 3% patients had positive family history which is less compared to other studies done previously.